Analisis Komitmen dan Kompensasi terhadap Efektivitas Kerja: Studi Empiris pada Aparatur UPTD Puskesmas Bojong Rawalumbu - Rini Ardista; Aditya Putra Kusuma (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The high public demand for quality healthcare services requires health centers to improve employee work effectiveness. This study aims to analyze the influence of work commitment and compensation on employee work effectiveness at UPTD Puskesmas Bojong Rawalumbu. An explanatory quantitative approach was used with a total sampling technique involving 33 employees. Primary data were gathered via questionnaires and analyzed using multiple linear regression. The results indicate that work commitment and compensation simultaneously have a significant impact on work effectiveness, explaining 55.4% of the variance. Partially, work commitment has a positive and significant effect on work effectiveness. Conversely, compensation does not show a significant effect. These findings suggest that public health sector apparatuses are driven more by intrinsic motivation and professional dedication than financial incentives. Therefore, strengthening psychological bonds is essential to optimizing public service quality.